Exclusive Breastfeeding Promotion And Neuropsychological Outcomes In 5-8 Year Old Children From Uganda And Burkina Faso: Results From The PROMISE EBF Cluster Randomized Tria - Tumwine, James K.; Nankabirwa, Victoria; Ndeezi, Grace (PloS one, 2018)
The beneficial effects from exclusive breastfeeding (EBF) have been widely acknowledged. We assessed the effect of exclusive breastfeeding promotion by peer counsellors in Uganda and Burkina Faso, on cognitive abilities, social emotional development, school performance and linear growth among 5–8 years old children.